Embedded Life Cycle Costing Elements in Green Building Rating Tool - Khan, Jam Shahzaib; Zakaria, Rozana; Aminudin, Eeydzah; Adiana Abidin, Nur Izie; Mahyuddin, Mohd Affifuddin; Ahmad, Rosli (Salehan Institute of Higher Education, 2019)
Green Building rating tools are the essential need of this era, to cope up with the sustainable development goals, climate change, and natural resource degradation through buildings. Realization of green building incentives decently increased within past few decades with abrupt declination in real estate markets and economic depletion has decelerated the interest of investors towards the green building projects. This research calculates influence of costing elements in MyCREST (IS-design) using questionnaire survey distributed amongst qualified professionals (QP’S) of green buildings and expert practitioners. Firstly, factor score and then weightage factor was performed to produce the final result with weightage output for evaluating weighatge and ranking of the relevant criteria of MyCREST and life cycle cost elements respectively. It is found that the criteria of storm water management has weighatge of 0.236 as highest and criteria environmental management plan (EMP) as 0.061 as lowest. Research also identified another perspective by finding association of cost element at design stage of MyCREST and found that management cost is highly associated at design stage with the value of 87.7%. The outcome of this research will add value to green building development and map road towards sustainable development using green building tools to uplift quality of life. Furthermore, this paves a way to integrate various stages of MyCREST with life cycle costing tool to potentially contribute in evaluating cost association through green building rating tool.